USULAN PERBAIKAN PROSES PRODUKSI LAMPU LED BERBASIS LEAN MANUFACTURING UNTUK MENINGKATKAN OUTPUT DI PT XYZ - Nazela Afaf; Hardiana Widyastuti; Suhendi Irawan (Journal Industrial Engineering and Management (JUST-ME), 2026)
PT XYZ faces challenges in meeting the daily production target for LED lamps, with an average achievement of only 89% of the target of 400 units per day. This research aims to identify waste and design improvement proposals using a lean manufacturing approach within the DMAIC (Define, Measure, Analyze, Improve, Control) framework. Based on observations and Value Stream Mapping (VSM), a significant bottleneck was identified at station 3 with a cycle time of 255 seconds, triggered by rework activities and ergonomic constraints. The proposed improvements include standardizing work methods and optimizing tools to eliminate Non-Value Added (NVA) activities. Through these improvements, it is expected that assembly line efficiency will increase, allowing the total production target of 10,000 units to be completed on time.